KEMAMPUAN SOSIAL ANAK KELOMPOK BERMAIN DITINJAU DARI POLA PENGASUHAN ORANGTUA - Isabella Hasiana (incrementapedia, 2019)
This research can be informed by neightborsaround the residence that there were children who were not able to socialize with their peers. The aim of this study was to find out the social abilities of the children in the play group in terms of the pattern of Permissive Parenting. The subjects used in this study were two children with the same parenting pattern. (1) This research method uses descriptive Qualitative, so that it can explain in detail how the Socialization capabilities carried out by group children play with the pattern of Permissive Parenting from the Tuanua people. Observation and interview are data retrieval carried out in this study, (2) The results of this study get a new finding, where the first subject has not had a good development at this time, the habit of Permissive Parenting makes it difficult for children to Socialize and tend to be spoiled by their parents. While the second subject is equally nurtured with Permissive Parenting patterns, but the second subject has been able to achieve the desired Socialization according to the level of his age, the difference is in habituation to the second subject even though he is spoiled by his parents because of the first child but he is parents because of the first child but he is getting used to knowing which is good and bad so that children are able to reach their Social sense easily.